Home automation using Raspberry Pi through Siri enabled mobile devices - Celebre, Ana Marie D. (Animo Repository, 2016)
Home automation is a system that has the technology to control devices automatically in order to convene the desires of security, comfort and efficiency. On the other hand, voice-based digital assistant such as Apple's Siri provides a location independent access to the Internet and local networks. This study focuses on implementing a home automation system through Siri's capability of speech recognition and through Raspberry Pi as a low cost control system to automate home devices, namely the air cooler, door, lights, TV and window. SiriProxy is installed on the Raspberry Pi as a proxy server for Siri. By developing a SiriProxy plug-in, a set of commands for home automation could be custom-made by the user. The system has been tested and verified through speech recognition's accuracy tests, response latency tests and success rate tests. A total of 34 subjects with different English accents tested a total of 14 voice commands with a total of 390 trials. The tests verified that the system's average latency is at 2.12 seconds with an overall success rate at 93.3333% on at least 3 trials and 87.381% success rate on at least one trial. © 2015 IEEE.